Development and validation of a device for monitoring laryngeal motion during swallowing - Aihara, Keiko; Inamoto, Yoko; Saitoh, Eiichi; Shibata, Seiko; Sato, Yuriko; Harada, Maki; Otaka, Yohei (Frontiers in Robotics and AI, 2023)
Objectives: Hyolaryngeal movement during swallowing is essential to airway protection and bolus clearance. Although palpation is widely used to evaluate hyolaryngeal motion, insufficient accuracy has been reported. The Bando Stretchable Strain Sensor for Swallowing (B4S™) was developed to capture hyolaryngeal elevation and display it as waveforms. This study compared laryngeal movement time detected by the B4S™ with laryngeal movement time measured by videofluoroscopy (VF). Methods: Participants were 20 patients without swallowing difficulty (10 men, 10 women; age 30.6 ± 7.1 years). The B4S™ was attached to the anterior neck and two saliva swallows were measured on VF images to determine the relative and absolute reliability of laryngeal elevation time measured on VF and that measured by the B4S™. Results: The intra-class correlation coefficient of the VF and B4S™ times was very high [ICC (1.1) = 0.980]. A Bland–Altman plot showed a strong positive correlation with a 95% confidence interval of 0.00–3.01 for the mean VF time and mean B4S™ time, with a fixed error detected in the positive direction but with no proportional error detected. Thus, the VF and B4S™ time measurements showed high consistency. Conclusion: The strong relative and absolute reliability suggest that the B4S™ can accurately detect the duration of superior-inferior laryngeal motion during swallowing. Further study is needed to develop a method for measuring the distance of laryngeal elevation. It is also necessary to investigate the usefulness of this device for evaluation and treatment in clinical settings.